Answer:
x = 3
General Formulas and Concepts:
Pre-Algebra
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
Equality Properties
Explanation:
Step 1: Define Equation
17 - (3x + 5) = 3x - 6
Step 2: Solve for x
- Distribute negative: 17 - 3x - 5 = 3x - 6
- Add 3x on both sides: 17 - 5 = 6x - 6
- Combine like terms: 12 = 6x - 6
- Isolate x term: 18 = 6x
- Isolate x: 3 = x
- Rewrite: x = 3
Step 3: Check
Plug in x into the original equation to verify it's a solution.
- Substitute in x: 17 - (3(3) + 5) = 3(3) - 6
- Multiply: 17 - (9 + 5) = 9 - 6
- Add: 17 - 14 = 9 - 6
- Subtract: 3 = 3
Here we see that 3 does indeed equal 3.
∴ x = 3 is the solution to the equation.